If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 7 + -1x + -14 = 0 Reorder the terms: 7 + -14 + 4x + -1x = 0 Combine like terms: 7 + -14 = -7 -7 + 4x + -1x = 0 Combine like terms: 4x + -1x = 3x -7 + 3x = 0 Solving -7 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 3x = 0 + 7 3x = 0 + 7 Combine like terms: 0 + 7 = 7 3x = 7 Divide each side by '3'. x = 2.333333333 Simplifying x = 2.333333333
| m^2+6m+4=0 | | ln(x+2)+ln(x)=ln(12+x) | | 3-5x+8=-2 | | 2x^2-18x=-2x^2-7x-6 | | 11-4y=-9 | | y+5=2y-3 | | 3+3x=x+13 | | 2(2d+5)=3(8-d) | | n^2-18n+81=40 | | X-2+4x=38 | | Cx+hy= | | (A-9)(2a-1)=0 | | 25600p=(p+12)(-p+20) | | -3b+-b= | | bx+hy=kforx | | 9p+2=4p-11 | | c=1/2mr | | -10x+50=400 | | 42/b=14 | | 27+3y-11=15y-12-5y | | -4.9x-6=-4.1x+2 | | 3(-2)-y=2 | | 100+10= | | 5n-2=-32 | | 7(k+8)+8=2 | | 2(2z-2)-2(3-4z)=4 | | log(6)36=4x+4 | | 20/14=t/35 | | a^7b^6-a^5b^4+a^4b^9-a^4b^4= | | 7v-9=10+6(v+7) | | 3z=2.9+0.4 | | -15x-3y=5 |